Immersed in our narratives: a study of the effectiveness of cobrand anthropomorphism - Han, Jie; Yun, Lexin; Wang, Yaming (Frontiers in Communication, 2025)
Anthropomorphism strategies have been widely applied in brand marketing activities such as advertising, service communication, and word-of-mouth, and have become an important marketing strategy for many brands. However, prior research has focused on single-brand contexts, leaving the effects and mechanisms of co-brand anthropomorphism underexplored. Drawing on anthropomorphism theory and narrative transportation theory, this study constructs a model to examine how co-brand anthropomorphism influences consumers’ evaluations and intentions toward co-branded products. Three experimental studies were conducted. The studies show that: Compared to non-anthropomorphism, anthropomorphism significantly enhances consumers’ evaluations and purchase intentions for co-branded products, with narrative transportation mediating this effect. The type of co-branding appeal moderates the results: anthropomorphism is effective for abstract appeals but not for specific appeals. The findings offer practical insights for brands to leverage anthropomorphism in co-branding campaigns, improving ad persuasion effectiveness.